Glíridos fósiles de Italia: situación actual - Kotsakis, Tassos (Coloquios de Paleontología, 2003)
In this paper the fossil glirids of Italy are reviewed. Non-endemic species of the family are known from sites of Turolian, Villanyian and Biharian age but their remains are rare. In Toringian, mammal assemblages are more common and micromammalian associations of this period are better known. The peculiar endemic glirids characterising mammalian assemblages of low biodiversity in insular environment are more interesting. Endemic species are present in the Early Miocene of Oschiri (Sardinia), in the Late Miocene of the Tusco-Sardinian palaeobioprovince and of the Abruzzi-Apulian palaeobioprovince, in the Plio-Pleistocene of Sardinia and of Sicily and in the late Pleistocene of Capri Island.
Keywords: Glirdae (Rodentia); Neogene; Quaternary; Italy